STUDI PERBANDINGAN ADSORPSI ION LOGAM Cd2+ PADA AF, Fe3O4 DAN Fe3O4-AF - Ririn Dwi Mardianto; Soerja Koesnarpadi; Ika Yekti Liana Sari (PROSIDING SEMINAR KIMIA, 2022)
Research on comparative study of metal ion adsorption on AF, and -AF has been carried out. The initial stage is the extraction of AF from the peat soil of the Samboja area of ​​East Kalimantan. Extraction was carried out with 1 M NaOH and 12 M HCl solution. The second stage was the preparation of dan -AF by coprecipitation method. The next step is the comparison test of AF adsorption, and -AF against metal ions. The results showed that -AF had 4 times greater adsorption ability than and AF in adsorption of metal ions that is equal to 8.4563 mg/g. This is because AF has a high affinity for particles and is able to increase the stability of Nano dispersion of by preventing their aggregation so that -AF is more dispersed and more stable. -AF also has a smaller size compared to AF and Fe3O4. Keywords: Adsorption, AF, Fe3O4, Fe3O4-AF, Cd2+